Високоефективна система відбору потужності для фотоелектричної станції - Зайцев, Роман Валентинович; Сокол, Євген Іванович; Хрипунов, Геннадій Семенович; Кіріченко, Михайло Валерійович; Прокопенко, Дмитро Сергійович (Інститут відновлюваної енергетики НАН України, 2016)
Проведено аналіз роботи системи відбору потужності для фотоелектричної станції з використанням підвищувального перетворювача. Показано, що коефіцієнт корисної дії такої системи в широкому діапазоні освітленості фотоелектричного модуля знаходиться нарівні 92%, тоді як ефективність класичних систем відбору потужності не перевищує 70%. Розроблено принципову електричну схему регульованого мостового резонансного підвищуючого перетворювача з цифровим керуванням, що забезпечує надійність роботи, швидке і точне знаходження точки максимальної потужності та ефективність перетворення до 96%.

To ensure maximum production of electric power by a photovoltaic station, which is, equipped with high-performance photo energy modules we propose to develop a highly efficient power take-off system. The most important part of the proposed power take-off system is a step-up boost converter, which provides a high transmission and transformation of electricity by increasing the DC voltage generated by photo energy modules. The aim of the work was a developing of constructive and circuit solutions and working parameters calculation of high- voltage power take-off system for photovoltaic energy station. During the performance it has been investigated the dependence of electrical power generated by photo energy modules from the intensity of solar radiation, it has been carried out the calculation of the parameters of the step-up boost converter and designed its circuit diagram also it has been analyzed the working features of power take-off using a step-up boost converter. By the results of experimental studies the samples of photo energy modules with a power of solar radiation from 1000 up to 2000 W/m2 it has been established that at the radiation power of 1700 W/m2 tested modules working with maximum efficiency at 16.89% and generates maximum electric power up to 419 W, which is 1.7 times more than power, generating by classic solar panels. Based on the obtained experimental data and results of LLC resonant circuit of step-up boost converter parameters calculations it has been designed the circuit diagram of bridge resonant digitally controlled step-up boost converter which efficiency reaches up to 95.8%. The analysis of the photovoltaic energy station power take-off system using a step-up boost converter working efficiency it has been carried out. It was shown that the efficiency of such a system in a wide range of photo energy module illumination power is at 92%, whereas the efficiency of classic power take-off systems does not exceed 70%.
High efficiency power take-off system for the photovoltaic energy station
Keywords: електрична енергія; фотоелектричні модулі; підвищуючі перетворювачі; струм; напруга; випромінювання; energy plant; photoenergy module; step-up converter; efficiency; electrical circuit